(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Phraseological units reflect the national mentality, the national worldview of native speakers, and this explains the increased interest of scientists in phraseology. The society and the language are inseparable and all historical events in the life of the society, the culture are reflected in the language of the people, in the form of lexemes containing information about the peculiarities of habitat, state structure of the society, cultural inside. The certain ethnic or linguistic communities’ background knowledge is the subject of investigation of linguistic and cultural studies. Among phraseological units of the English language, about 400 phraseological units (with an open list) describe speech behavior. Phraseologisms of this type are the object of our study. The phraseological units of behavior that characterize the manner of speech communication include such phraseological units as, for example, “gibber like an ape”; “talk through the back of one’s neck”; “not to breathe a syllable (word)”; “put a bridle on (one’s tongue)”; “talk nineteen (twenty or forty) to the dozen”; “Has the cat got your tongue?” In our article, from such phraseological units of speech behavior, we are interested in a subgroup of phraseological units reflecting household realities.